Chemometrics : data analysis for the laboratory and chemical plant - Brereton, Richard G (Chichester, West Sussex, England ; Hoboken, NJ : Wiley, 2003)
This title is aimed at people who need to use chemometrics but do not wish to understand complex mathematics. It includes worked problems and two dedicated chapters explaining how to analyse data sets using the most common chemometrics packages
Points of View -- Software and Calculations -- Experimental Design -- Degrees of Freedom -- Analysis of Variance and Comparison of Errors -- Design Matrices and Modelling -- Assessment of Significance -- Leverage and Confidence in Models -- Factorial Designs -- Full Factorial Designs -- Fractional Factorial Designs -- Plackett-Burman and Taguchi Designs -- Partial Factorials at Several Levels: Calibration Designs -- Central Composite or Response Surface Designs -- Setting Up the Design -- Degrees of Freedom -- Axial Points -- Modelling -- Statistical Factors -- Mixture Designs -- Mixture Space -- Simplex Centroid -- Simplex Lattice -- Constraints -- Process Variables -- Simplex Optimisation -- Fixed Sized Simplex -- Elaborations -- Modified Simplex -- Limitations -- Signal Processing -- Sequential Signals in Chemistry -- Environmental and Geological Processes -- Industrial Process Control -- Chromatograms and Spectra -- Fourier Transforms -- Advanced Methods -- Peakshapes -- Digitisation -- Noise -- Sequential Processes -- Linear Filters -- Smoothing Functions -- Derivatives -- Convolution -- Correlograms and Time Series Analysis -- Auto-correlograms -- Cross-correlograms -- Multivariate Correlograms -- Fourier Transform Techniques -- Fourier Transforms -- Fourier Filters -- Convolution Theorem -- Topical Methods -- Kalman Filters -- Wavelet Transforms -- Maximum Entropy (Maxent) and Bayesian Methods -- Pattern Recognition -- Exploratory Data Analysis -- Unsupervised Pattern Recognition
Includes bibliographical references (pages 12-13) and index
Keywords: Chemometrics -- Data processing; Chemical processes -- Statistical methods -- Data processing